Negotiation of the global grid inspection UAV with random delay uncertainty in an information communication network based on a robust fault tolerance mechanism - Shen, Jie; Dong, Wen qi; Wang, Zhi-fang; Wang, Jing; Wang, Yang; Liu, Han min; Li, Haiyan (Frontiers in Aerospace Engineering, 2023)
In order to accurately simulate the interference mechanism of information communication between the unmanned aerial vehicles (UAV) in the future global grid system, a kind of control based on the dynamic simulation of satellite communication network and robust fault tolerance with stochastic delay uncertain network system is proposed. Based on the imaginary future of the global energy Internet background of unknown information and communication interference, we establish the UAV model from the sensor to the actuator network delay on the robust fault-tolerant control algorithm and the satellite communication network model that combines the controller’s mathematical model. The simulation results show that the power transmission capability and the communication coverage ability of the UAV are improved by using the network fault-tolerant control mechanism with uncertain network delay under the information communication interference. The stability and anti-interference performance has also been significantly improved. The algorithm can provide a certain strategy for the development of future global energy Internet.